Design of an Integrated Near-Field Communication and Wireless Power Transfer Coupler for Mobile Device Applications - Hongguk Bae; Sangwook Park (Technologies)
In this study, we propose a model that integrates a near-field communication (NFC) coupler and a wireless power transfer (WPT) coupler for mobile device applications. The NFC and WPT couplers were independently designed and then combined into a four-port NFC–WPT coupler. The proposed practical equivalent circuit (PEC) introduces a novel multi-port network representation, where inductive and capacitive coupling structures are modeled using T-model and Pi-model configurations, respectively. Based on this circuit model, we present a detailed theoretical approach for deriving a 4 × 4 S-parameter matrix by converting the transmission matrices of the partitioned circuit networks into S-parameters. The comparison between the theoretical analysis and the simulation results shows an error of less than 2.4%, which demonstrates the high accuracy of the proposed method.